2008
DOI: 10.1007/s10719-008-9113-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipid binding epitopes involved in adherence of the periodontitis-associated bacterium Porphyromonas gingivalis

Abstract: The ability of the periodontal pathogen Porphyromonas gingivalis to use different glycolipid structures as receptors has previously been demonstrated. The bacterium adhered to acid and nonacid glycolipids originating from human organs and to nonacid glycolipids of porcine origin. The aim of the present study was to analyze these binding epitopes by structural characterization. Glycolipid fractions with positive bacterial binding from e.g. human and porcine origin, were purified by the high performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Table 3. Fraction 121:I thus contains two monohexosylceramide species identified as Glc␤1Cer (structure 1) (ϳ90%) and Gal␤1Cer (structure 2) (ϳ10%) from the positions of the anomeric resonances at 4.075 and 4.024 ppm, respectively (25). The glucose is corroborated by the observation of its H2 resonance at 2.996 ppm (data not shown).…”
Section: Characterization Of Mono- Di- and Triglycosylceramides Fromentioning
confidence: 80%
See 2 more Smart Citations
“…Table 3. Fraction 121:I thus contains two monohexosylceramide species identified as Glc␤1Cer (structure 1) (ϳ90%) and Gal␤1Cer (structure 2) (ϳ10%) from the positions of the anomeric resonances at 4.075 and 4.024 ppm, respectively (25). The glucose is corroborated by the observation of its H2 resonance at 2.996 ppm (data not shown).…”
Section: Characterization Of Mono- Di- and Triglycosylceramides Fromentioning
confidence: 80%
“…The subsequent fraction (121:II) displays anomeric resonances from three different glycosphingolipids: globotriaosylceramide (structure 5) (ϳ45%), as evidenced by resonances at 4.780 ppm (Gal␣4), 4.246 ppm (Gal␤4), and 4.157 ppm (Glc␤1); galabiaosylceramide (structure 4) (ϳ10%) with anomeric resonances at 4.814 ppm (Gal␣4) and 4.098 ppm (Gal␤1); and finally, lactosylceramide (structure 3) (ϳ45%) with resonances at 4.195 (Gal␤4) and 4.155 ppm (Glc␤1), the latter completely overlapping the corresponding globotriaosylceramide resonance (25,26). In fraction 121:III, only one additional compound is evident, namely globotetraosylceramide (structure 6), whose minor resonances (ϳ5% of the dominating globotriaosylceramide contribution) are found at 4.797 ppm (Gal␣4), 4.514 ppm (GalNAc␤3), 4.26 ppm (Gal␤4), and 4.16 ppm (Glc␤1) (25).…”
Section: Characterization Of Mono- Di- and Triglycosylceramides Fromentioning
confidence: 99%
See 1 more Smart Citation
“…, 2011) whereas pretreatment of human cells with sialidase or incubation with sialic acid reduces invasion (Agnani et al. , 2000; Hallen et al. , 2008).…”
Section: Sialidases Appear To Be Multifunctional Virulence Factors Fomentioning
confidence: 99%
“…Furthermore, we have shown that P. gingivalis can bind to both acidic and non‐acidic glycolipid fractions from a variety of organs of human and porcine origin, with a preference for sulfated glycolipids (11). We have also shown a preference for P. gingivalis to bind to cerebroside with non‐hydroxy fatty acid, as compared with gastrointestinal bacteria, which prefer hydroxy fatty acid (10). The aim of this present study was to investigate the ability of the periodontal pathogen P. gingivalis to adhere to glycoconjugates on intact cells and to glycoprotein preparations of epithelial cells.…”
mentioning
confidence: 84%